CORAK PEMBARUAN PEMIKIRAN HUKUM ISLAM DALAM KONSEP “FIQH SOSIAL” K.H SAHAL MAHFUDH - Reza Fauzi Nazar (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2021)
Abstract: The social fiqh K.H Sahal Mahfudh is a thought that was born from pesantren tradition. Social fiqh in fact is projected to redesign the stagnated fiqh in pesantren with the nuances of madzhabi fiqh which are considered less responsive to social problems, and to counter-discourse a